The causality relationship between capital structure and profitability in general insurance industry in Indonesia - Suhartono, Suhartono (International Journal for Educational and Vocational Studies, 2022)
Many researchers have found that there is a significant influence of the main components of capital structure on corporate leverage and company profitability. The studies conducted generally only examine a single relationship, so the conclusions obtained are not comprehensive. Based on this, this research will examine the effect of simultaneous capital structure such as growth opportunities (PP), company size (UP), tangible assets (AT), company liquidity (LP), and business risk (RB) on Debt Equity Ratio (DER) ) and the influence of capital structure such as growth opportunities (PP), company size (UP), tangible assets (AT), company liquidity (LP), and business risk (RB) on Debt Equity Ratio (DER) of general insurance companies in Indonesia and leverage on the profitability of general insurance companies in Indonesia. The analytical method used in this study is the path analysis method. Through the path analysis method will be known the magnitude of the causality relationship between variables. Based on the results of the analysis it is known that growth opportunities (PP), company size (UP), and company liquidity (LP) negatively affect Debt Equity Ratio (DER). Tangible assets (AT) and business risk (RB) have a positive effect on Debt Equity Ratio (DER). Whereas Debt Equity Ratio (DER) has a negative effect on the profitability of general insurance companies (PRO) in Indonesia. Related to the profitability of the analysis results it is known that growth opportunities (PP), company size (UP), reliable assets (AT), company liquidity (LP), and business risk (RB) have a positive effect on the profitability of the company (PRO) of general insurance in Indonesia.